How effective is outpatient care compared to inpatient care for the treatment of anorexia nervosa? A systematic review - Meads, C; Gold, L; Burls, A (2001)
Objective: To review systematically inpatient compared to outpatient care for the treatment of anorexia nervosa and other eating disorders. Method: Search of electronic databases, references and contact with experts to identify randomized controlled trials (RCTs), case-control studies and case series. Study quality was assessed and data extracted by two independent researchers. Results: Two RCTs and seven case series were identified. Unpublished 5-year follow-up data from one RCT showed a (non-statistically significant) improvement in percentage well in the outpatient compared to the inpatient group, but no difference in mortality. Case series were difficult to interpret because of the inherent biases - follow-up varied from 1.5 to 11.7 years and showed wide variations in outcome. Discussion: There is no evidence that inpatient treatment is more (or less) effective than outpatient treatment for people with anorexia nervosa in the long term. Short-term emergency inpatient treatment of the consequences of eating disorders may still be necessary. Copyright © 2001 John Wiley and Sons, Ltd and Eating Disorders Association.